THE SECOND CAMPAIGN OF NADIR-SHAH INTO DAGHESTAN (ON MATERIALS OF"ALAMARA-YE NADERI" BY MUHAMMAD KAZIM MERVI) - Alibekova, Patimat Magomedovna (History, Archeology and Ethnography of the Caucasus, 2018)
The article contains materials from the Persian composition of Muhammad Kazim Mervi "Alamara-ye Naderi" (The history of Nadir-shah that beautifies the world), published in Tehran in 1364/1985 in 3 volumes which were not translated into Russian before. The composition of Muhammad Kazim Mervi is a valuable source, which contains 16 chapters on the military campaigns of Nadir Shah into Daghestan. The value of this work is in its pithiness, impartiality and relative objectivity in the narration of events. This source is important for the reconstruction of historical events that took place in the first half of the 18th century. The article presents one of the periods of the heroic liberation struggle of the peoples of Daghestan and the Jar-tala societies against the ruler of Iran Nadir-shah Afshar for many years. The isolation and disunity of the rulers of the Daghestani feudal societies served to the fact that their struggle against the expansion of Nadir-shakh took a protracted character. The tactics of offensive and retreat, the manifastation of obedience, often ostentatious, were widely used by the Daghestani rulers for their strategic purposes. Description of the second campaign of Nadir Shah into Daghestan, which occurred in November 1735, reproduces one of the stages of the road to the complete rout of Nadir Shah's troops in Daghestan. The article contains a translation of the chapter on the second military campaign of Nadir Shah into Daghestan, comments on the text are given.
Keywords: the history of Daghestan; the history of Iran; military campaigns; Persian texts; the people's liberation struggle